2008
DOI: 10.1007/s00268-008-9837-9
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Resection Improves Perception of Swallowing Function in Patients with Thyroid Disease

Abstract: Background Patients with thyroid disease frequently complain of dysphagia. To date, there have been no prospective studies evaluating swallowing function before and after thyroid surgery. We used the swallowing quality of life (SWAL-QOL) validated outcomes assessment tool to measure changes in swallowing-related quality-of-life in patients undergoing thyroid surgery. Methods Patients undergoing thyroid surgery from May 2002 to December 2004 completed the SWAL-QOL questionnaire before and one year after surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
59
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 26 publications
8
59
1
Order By: Relevance
“…Swallowing dysfunction is a commonly reported symptom in pre-operative thyroidectomy patients, with the majority complaining of a globus sensation [1,[3][4][5]7,18]. In our cohort, 47.2% of patients reported swallowing symptoms at least some of the time, with 27.1% reporting symptoms often or always; with the majority of symptoms relating to a globus sensation.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Swallowing dysfunction is a commonly reported symptom in pre-operative thyroidectomy patients, with the majority complaining of a globus sensation [1,[3][4][5]7,18]. In our cohort, 47.2% of patients reported swallowing symptoms at least some of the time, with 27.1% reporting symptoms often or always; with the majority of symptoms relating to a globus sensation.…”
Section: Discussionmentioning
confidence: 65%
“…A literature review found that the reported prevalence of compressive symptoms in pre-operative thyroidectomy patients varied widely between studies, ranging from 11-88% [1][2][3][4][5][6][7]. Unfortunately many of these studies vary with regards to the symptoms reported as well as the methods used for data collection (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nodular goiter can lead to a wide range of symptoms including swallowing discomfort and respiratory disturbances, which can have a negative impact on quality of life (QoL) [1, 5, 6]. A clear correlation between goiter volume, tracheal compression, and relief from this compression following thyroidectomy is seen in patients with benign goiter [7], but little is known concerning the impact of goiter on the esophagus.…”
Section: Introductionmentioning
confidence: 99%